Ethnobotanical study of medicinal plants in the Fez-Meknes region of Morocco - Sara Tlemcani; Amal Lahkimi; Noureddine Eloutassi; Ahmed Bendaoud; Anouar Hmamou; Hicham Bekkari (GarVal Editorial Ltda., 2023)
Context: The region of Fez-Meknes has a wide variety of aromatic and medicinal plants that can be explored in different ways to draw their virtues and overcome human health problems. Aims: To identify ethnobotanically the main medicinal plants and collect data about their uses in the region of Fez. Methods: During each interview, both the personal information and the plants used were collected. The questionnaire revealed the use frequency of each part of the plants (VPP). It also sheds light on the importance of each species (RFC). Furthermore, it showed the relative importance of the families and the method of preparation (FIV). Results: The results disclosed the richness of the region in terms of medicinal plants. A total of 57 species were identified and grouped into 24 families. The most abundant families were Lamiaceae (FIV = 5.461), Compositae (FIV= 6.085), and Apiaceae (FIV = 6.307). The most cited species were Plantago major L. (RFC = 27.3%), Olea europaea L. (RFC = 31.3 %), and Daphne gnidium L. (RFC = 32.6%). The leaves are the most plant part used (VPP = 0.416). The most used preparation method was decoction (32%). The most declared pathologies were digestive (16%), dermatological (15%), and respiratory affections (13%). Conclusions: The ethnobotanical study showed the region's floristic richness and allowed the identification of the different plants involved in many recipes to overcome human health problems.